2015
DOI: 10.1097/wnr.0000000000000353
|View full text |Cite
|
Sign up to set email alerts
|

Improving proactive control with training on language switching in bilinguals

Abstract: The present study examined how a short period of language switching training affects nonverbal cognitive control, as measured by the AX version of the Continuous Performance Test. A group of Chinese-English bilinguals were trained over 10 days on a picture naming task that required switching between languages. We recorded their behavioral performance and event-related potentials before and after the training to examine its effects on cognitive performance. The behavioral measurement of proactive control, that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 25 publications
6
48
0
Order By: Relevance
“…One possibility is that short‐term language switching training is more likely to modulate the general conflict monitoring process, resulting in both a training effect and a transfer effect. This speculation is consistent with the findings of two studies from our group [Kang et al, ; Zhang et al, ]. In the ERP study using a similar design, Kang et al [] found that the peak latency of cue‐locked N2, a negativity peaking around 200–300 ms after cue onset, was significantly shortened after 8‐day language switching training.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…One possibility is that short‐term language switching training is more likely to modulate the general conflict monitoring process, resulting in both a training effect and a transfer effect. This speculation is consistent with the findings of two studies from our group [Kang et al, ; Zhang et al, ]. In the ERP study using a similar design, Kang et al [] found that the peak latency of cue‐locked N2, a negativity peaking around 200–300 ms after cue onset, was significantly shortened after 8‐day language switching training.…”
Section: Discussionsupporting
confidence: 89%
“…In another study, Zhang et al [] observed a far transfer effect of 10‐day language switching training in the AX‐Continuous Performance Task, which examines domain‐general executive control. Specifically, except for the behavioral improvement, an enhanced N2 for processing probe stimuli was found after training, indicating that language switching training improves the proactive aspect of domain‐general executive control in unbalanced bilinguals.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, like the go/no‐go task, bilingualism is associated with enhanced N2 on conflict trials in the AX‐CPT task. This pattern was also found in a study of two groups of young adult bilinguals in which one group received practice in language switching; both groups performed the AX‐CPT at two time intervals . ERPs were first recorded to get a measure of baseline performance.…”
Section: Earlier and More Automatic Processes In Bilingualsmentioning
confidence: 99%
“…This pattern was also found in a study of two groups of young adult bilinguals in which one group received practice in language switching; both groups performed the AX-CPT at two time intervals. 112 ERPs were first recorded to get a measure of baseline performance. Following this, the experimental group received languageswitching practice for 10 days, but the control group did not.…”
Section: Earlier and More Automatic Processes In Bilingualsmentioning
confidence: 99%
“…Along the same lines, second language learning, even for older post-critical period speakers can be viewed as one type of cognitive training that capitalizes on inhibitory control and other executive functions (comparable to other activities such as video game playing). Zhang et al (2015) examined how a short period of language switching training could affect measures of nonverbal proactive and reactive cognitive control. Twenty-eight young Chinese-English bilinguals (and 28 Chinese-English bilinguals for the control group) were trained for a period of ten days using a cued picture naming task, during which bilinguals named pictures either in Chinese or English according to the color of the frame.…”
Section: Merging Bilingualism Into Aging: Future Research Directionsmentioning
confidence: 99%